Multimedia Berbasis Video Tutorial Pada Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan (PJOK) Kelas X - Srinarti Srinarti; Joko Kuswanto (Universitas Baturaja, 2023)
This research aims to produce multimedia based on video tutorials on the subject of physical education, sports and health (PJOK) class X. Data collection techniques use expert validation sheets and field trials, in the form of questionnaires and documentation. Based on the results of the validation, the three experts obtained the